2002
DOI: 10.1177/026835550201700108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Posture on the Pressure Exerted by Below-Knee Class II Compression Stockings on Normal Subjects

Abstract: Background: Below-knee elastic compression stockings are widely used for the treatment of chronic venous insufficiency. The exact amount of pressure exerted by these stockings on different parts of leg and in different postures remains controversial. Objective: To examine the pressure exerted by correctly fitted class II below knee compression stockings at different levels and postures in normal subjects. Methods: Seven healthy human volunteers (mean age 38 years) were fitted with CEN class II below-knee compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“… quality control of (new) compression products and/or compression techniques, 4,8,11,14,27,35–44 proof of concepts (e.g., do we apply graduated compression? ), 31,39,45,46 comparative clinical trials (to assess the “dosage” of compression applied to individual legs), 8,47 correlation with clinical outcomes or with physiological measurements, 6,24,38,48–56 documentation of clinical care (continuous monitoring), 8,19,43,57 training individuals how to apply compression bandages, 9,58–60 classification of compression bandages, compression stockings, velcro‐straps, multi‐layer compression systems, 8,71 validation of in vitro measurements, 20,30,56,61,62 compression of stockings to be indicated in mmHg instead of compression classes, 63 evaluation of the level of compression of a bandage, a stocking or a device over time 8,19,41,43,44,57 …”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… quality control of (new) compression products and/or compression techniques, 4,8,11,14,27,35–44 proof of concepts (e.g., do we apply graduated compression? ), 31,39,45,46 comparative clinical trials (to assess the “dosage” of compression applied to individual legs), 8,47 correlation with clinical outcomes or with physiological measurements, 6,24,38,48–56 documentation of clinical care (continuous monitoring), 8,19,43,57 training individuals how to apply compression bandages, 9,58–60 classification of compression bandages, compression stockings, velcro‐straps, multi‐layer compression systems, 8,71 validation of in vitro measurements, 20,30,56,61,62 compression of stockings to be indicated in mmHg instead of compression classes, 63 evaluation of the level of compression of a bandage, a stocking or a device over time 8,19,41,43,44,57 …”
Section: Indicationsmentioning
confidence: 99%
“…After application of the compression device, pressures should be measured with the patient in both supine and standing positions 8,19,35,42,45,68 . Pressures may also be measured when the calf muscle and ankle joint pump are activated 13,15,19,27,28,48,66 .…”
Section: Body Positions To Measure the Pressures Under The Devicesmentioning
confidence: 99%
“…There is now a consensus 4 of medical and technical experts concerning the evaluation methods of compressive hosiery according to which measurement of the pressure exerted is important or even essential within the context of clinical trials. Some studies of compression stockings have provided results of in situ pressure measurements 5–25 . These studies were performed using different procedures and measuring systems, which makes comparison of results difficult.…”
mentioning
confidence: 99%
“…A huge part of research on compression stockings is related to their medical usage [7][8][9] and published in medical scientific journals [9][10][11] because of medical aspects' study. It was found that the pressure profile exerted by elastic stockings varies with the posture [12] and exercise [13]. Furthermore, the changes in pressure vary from side to side of the leg.…”
Section: Introductionmentioning
confidence: 99%